IMAJINASI DESA IMPIAN: Konstruksi Media dalam Pengembangan Desa Wisata di Desa Ranuklindungan Kabupaten Pasuruan - Sulis Tia Ningsih; Ucha Jaya Sucipta Jaya Sucipta; Maurina Suryaning Pertiwi (The Journal of Society and Media, 2018)
The visualization of Rural development today is largely the result of mass media construction, as evidenced by the proliferation of village tourism as a pilot village for other regions. Indirectly the media will represent the ideal Village so that the development that is formed today can not be separated from the interference of mass media.Urgensi of this research is to see the ideal Village development which is sometimes considered to be opposite with the opinions and expectations of the community. The main purpose of this research is to describe how the Village Elite, PKK group and Local heroes who play a role in mobilizing the community to build and improve the area of origin independently. They are the subject of research studies in envisioning their own version of the ideal Village in the middle of the tourism tour, the construction of toll roads, theconstruction of the framming of mass media and further describing the role of media in theideal Village in the wider community. The research uses qualitative descriptive method when it is considered important to be done considering the majority of development today based on the interests but the face of equity welfare. The result of this research is the inclusion of the Tourism Village to be the reason to change the face of the careless suburban village with the environment into environmentally conscious tourism village as well as eliminating the 'Village' entity itself, further mass media becomes an instrument to construct and build people's critical reason